Subjective well-being in non-obese individuals depends strongly on body composition - Małgorzata Chlabicz (Nature Portfolio, 2021)
Abstract While obesity has been correlated with welfare in the general population, there is not much data on the influence of body composition on welfare among the non-obese adult individuals. In this study, a total of 726 non-obese individuals from the general population were analyzed. The mean age was 46.8 ± 15.4 years and 42.1% of participants were male. The anthropometric measurements and dual energy X-ray absorptiometry (DEXA) were done. The mean value for the Satisfaction with Life Scale (SWLS) was 23.09 ± 5.43, for Euro Quality of Life Visual Analogue Scale (EQ-VAS) was 78.0 ± 14.5, and for the Beck Depression Inventory (BDI) was 6.7 ± 6.6. On the SWLS, the higher waist-hip ratio had a negative impact even after adjusting for age, gender, and concomitant diseases. EQ-VAS was inversely associated with android fat distribution and directly associated with muscle mass. BDI value was inversely associated with lower muscle mass, especially in lower limbs. The well-being of women was mainly associated with the distribution of adipose tissue and less with the distribution of muscle tissue—abdominal fat distribution has a particularly negative impact on well-being among women. In contrast, men’s well-being depends more on muscle mass and to a lesser extent on the distribution of fat tissue—a positive significant effect has lean mass and a circumference of thigh below gluteal fold.